Strategi Humas Soul Puncak Lawang Meningkatkan Dalam Pengunjung Wisata Alam Puncak Lawang Di Masa Pandemi Covid-19 - Fauziah Lagusti; Ria Edlina (CV. ITTC INDONESIA, 2023)
Strategy is an integrated part of a plan (plan), while the plan is the product of a plan (planning), which in the end planning is one of the basic functions of the management process. Strategy is often used in determining a goal to be achieved. Likewise with marketing and advertising activities. The planning strategy in the field of public relations includes the following activities: 1) making decisions regarding program goals and objectives, 2) identifying the determining audience, 3) establishing policies or rules to determine the strategy to be chosen, deciding which strategy to use. The strategy is useful as a plan in dealing with a condition, in this case the research conducted is to see how the Puncak Lawang Public Relations strategy increases visitors after being hit by the Covid19 pandemic.This study uses qualitative methods to describe PR strategies in increasing visitor returns, while the data collection techniques used by researchers are observation and in-depth interviews. Interviews were conducted with the owner of the Puncak Lawang Soul, the Tourism Office, and the Public Relations of the Puncak Lawang Soul itself. The results of the study indicate that there are various strategies and approaches taken by the Public Relations of Soul Puncak Lawang, including: The persuasive educative approach and the cooperative approach, while the strategies used are: 1. Internal strategy: a. Following the CHSE Rules set by the Government (cleanliness, safety, environment sustainability). B. Complete Health Protocol Facilities (hand washing area, temperature check, hansanitaizer). C. Improving HR performance in the field of Public Relations (holding training, motivational seminars). 2. External strategy: a. Promotion through various media (online and offline media). 2. Cooperating (with various parties both for events and activities and other purposes) Public Relations Soul strives to improve the condition of the company both internally and externally, the role of Public Relations is very visible with the strategies that have been carried out and planned by PR Soul Peak Lawang itself.